SAT-170 Clinical Course of Adrenal Myelolipoma: A Long-Term Longitudinal Follow-Up Study - Hamidi, Oksana (J Endocr Soc, 2020)
Myelolipoma is the second most common adrenal tumor. Yet, systematic approach to these tumors remains poorly defined. Thus, we aimed to describe natural history of myelolipoma and to identify predictors of tumor growth and need for surgery. We conducted a retrospective longitudinal follow-up study of consecutive patients with myelolipoma. A total of 321 myelolipomas (median size, 2.3 cm [range, 0.5-18.0]) were diagnosed in 305 patients at median age of 63 years (25-87). Most myelolipomas were discovered incidentally (86.6%), whereas others were discovered on imaging done for cancer staging (8.8%) or during workup of mass effect symptoms (4.6%). Median duration of follow-up was 54 months (range, 0.03-267). Compared with myelolipomas <6 cm, tumors ≥6 cm were more likely to be right-sided (59% vs 41%, P=0.02), bilateral (21% vs 3%, P <.0001), cause mass effects symptoms (32% vs 0%, P<.0001), have radiographic hemorrhagic changes (14% vs 1%, P<.0001), and undergo adrenalectomy (52% vs 5%, P<.0001). There was no difference in sex or age at diagnosis between the groups. Hemorrhagic changes were noted in 9 (3.0%) patients with median tumor size of 7.0 cm (range, 1.8-18.0). Concomitant adrenal hormone excess was diagnosed in 12/126 (9.5%) patients. Primary aldosteronism was noted in 9 patients: due to concomitant ipsilateral (n=3) or contralateral adrenocortical adenoma (n=3), or bilateral idiopathic adrenal hyperplasia (n=3). Autonomous cortisol excess was noted in 3 patients: due to concomitant contralateral (n=2) or ipsilateral adrenocortical adenoma (n=1). Of 162 patients with ≥6 months of imaging follow-up, tumor size change ranged from -10 to 115 mm (median, 0 mm) and tumor growth rate ranged from -5.6 to 140 mm/year (median, 0 mm/year). Tumor growth ≥1.0 cm (n=26, 16.0%) was associated with larger initial tumor size (3.6 vs 2.3 cm, P=0.02) and hemorrhagic changes on imaging (12% vs 2%, P=0.007), compared with <1 cm size change. Myelolipomas with ≥1.0 cm growth were more likely to undergo adrenalectomy (35% vs 8%, P<.0001). Among 37 (12%) patients that underwent adrenalectomy for myelolipoma, surgical indications included: large tumor size/tumor growth (32%), diagnostic surgery (27%), mass effect symptoms (14%), concomitant ipsilateral tumor leading to hormonal excess (11%), acute hemorrhage (8%), and concomitant resection during non-adrenal surgery (8%). In conclusion, most myelolipomas are discovered incidentally, whereas myelolipomas ≥6 are more likely to cause mass effect symptoms, have radiographic hemorrhagic changes, and more commonly undergo resection. Hormonal excess is rare and is usually attributed to concomitant adrenocortical adenoma or hyperplasia. Tumor growth ≥1.0 cm is associated with larger myelolipoma and presence of hemorrhagic changes. Surgical resection should be considered in symptomatic patients with large tumors, evidence of hemorrhage, or tumor growth.